Mining of a CAD of space curves and kinematic surfaces - Василевський, О.В. (Proceedings of National Aviation University (archive), 2005)
The article is dedicated to problems of mining of a CAD of space curves of lines and kinematic surfaces on the basis of methods offered the author, of auxiliary surfaces which one will generate the form.